SCIENCE LEARNING MEDIA IN GRADE VI: AVAILABILITY, USAGE, AND EFFECTS ON ACADEMIC PERFORMANCE - HS, dyan wulan sari; Fauzi, KMS. Muhammad Amin; Dewi, Izwita (JURNAL DARMA AGUNG, 2024)
This research investigates the multifaceted dynamics surrounding the utilization of science learning media in Grade VI classrooms, focusing on their availability, patterns of usage, and subsequent impact on academic outcomes. By employing a quantitative descriptive research design, data were gathered through surveys, questionnaires, and interviews with science teachers. The study, innovative in its application of the RASCH Model, revealed a positive correlation between the use of science kits and students' UN Science scores. Noteworthy findings include the prevalence of science kits, the absence of science practicum laboratories, and the underutilization of available learning media. Moderating factors such as teacher training, urban-rural distinctions, gender-based differences, and teacher experience were also identified. While contributing valuable insights, the study emphasizes the need for future research to address gaps, particularly the characteristics of effective science kits and the perspectives of various stakeholders. This research serves as a foundation for enhancing science education methodologies and creating more effective learning environments in elementary schools.